2010
DOI: 10.1177/0022034510368784
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cells and Innate Antifungal Defense

Abstract: The human pathogenic fungus Candida albicans is the predominant cause of both superficial and invasive forms of candidiasis. Clinical observations indicate that mucocutaneous Candida infections are commonly associated with defective cell-mediated immune responses. The importance of the innate immune system as a first-line defense against pathogenic challenge has long been recognized. Over the last decade, many key molecules mediating innate host defense have been identified. Central to these developments is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 131 publications
(178 reference statements)
1
67
0
2
Order By: Relevance
“…74 However, only Dectin-1 is found expressed in epithelial cells. 75 Although some studies on other fungal pathogens have revealed the up-regulation of Dectin-1 in human epithelial cells upon fungal infection, 76,77 few studies work on the role of Dectin-1 in C. albicans recognition in epithelial cells up to now.…”
Section: Prrs Of Epithelial Cellsmentioning
confidence: 99%
“…74 However, only Dectin-1 is found expressed in epithelial cells. 75 Although some studies on other fungal pathogens have revealed the up-regulation of Dectin-1 in human epithelial cells upon fungal infection, 76,77 few studies work on the role of Dectin-1 in C. albicans recognition in epithelial cells up to now.…”
Section: Prrs Of Epithelial Cellsmentioning
confidence: 99%
“…67 Different groups of TLRs such as TLR2, TLR4, TLR6, and TLR9 are functionally expressed on the oral epithelium, highlighting the essential status of TLRs in oral defense. 68,69 TLR2 and TLR4 have been found to be elevated inside the inflamed gingivae. 70 TLR4 is found to be involved in the vaginal PMN recruitment response initiated by S100A8 alarmin.…”
Section: Epithelial Cellsmentioning
confidence: 99%
“…72 As for CLRs, dectin-1 is the only receptor that shows some effects in the recognition of human gingival epithelia. 69 Ligation of epithelial PRRs by invading pathogens is usually followed by the activation of cascade signaling, and the subsequent production of pro-inflammatory, growth factors and antimicrobial factors. It was found that oral and vaginal epithelial cells activate NF-kB and the biphasic MAPK (mitogen-activated protein kinase) pathway in response to the stimulation caused by C. albicans.…”
Section: Epithelial Cellsmentioning
confidence: 99%
“…Além dessa proteção passiva, as células epiteliais respondem ativamente, por meio de um processo inflamatório, secretando citocinas e quimiocinas que interagem com vários tipos celulares para ativação da resposta imune inata e, posteriormente, resposta imune adaptativa (ABIKO et al, 2007;DÉCANIS;SAVIGNAC;ROUABHIA, 2009;SCHALLER, 2010).…”
Section: Lista De Figurasunclassified
“…Com enfoque na imunidade inata em resposta a presença de microrganismos patogênicos, as células epiteliais produzem, além das citocinas, moléculas antimicrobianas que podem contribuir com o combate do patógeno antes da infecção se instalar (SEO et al, 2002;LU et al, 2006;ABIKO et al, 2007;SCHALLER, 2010 , além de participarem da modulação das respostas imunes inata e adaptativa contra vários patógenos bucais (DOSS et al, 2010). O óxido nítrico (NO), sintetizado por diversas células, incluindo queratinócitos, também é produzido em resposta à infecção microbiana (SEO et al, 2002), com um papel importante na defesa do hospedeiro contra C. albicans pela destruição celular direta ou formação de ânions (NAKAI; KUBOTA; KOSAKA, 2004).…”
Section: Lista De Figurasunclassified